ACTIVITIES OF DIPLOMATIC MISSION - Nodirbekov Davronbek; Qodirov Xalilulo; Egamberdiyeva iroda (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: A diplomatic mission or foreign mission is a group of people from a state or organization present in another state to represent the sending state or organization officially in the receiving or host state.[1] In practice, the phrase usually denotes an embassy, which is the main office of a country's diplomatic representatives to another country; it is usually, but not necessarily, based in the receiving state's capital city.[2] Consulates, on the other hand, are smaller diplomatic missions that are normally located in major cities of the receiving state.